Natural products for intervertebral disc degeneration: mechanistic insights and therapeutic potentials - Wu, Zenghan; Chen, Jiang; Luo, Wenhai; Kuang, Tao (Frontiers in Pharmacology, 2025)
Intervertebral disc degeneration (IDD) is a leading cause of spinal disorders worldwide. Current clinical therapies for IDD are often constrained by limited efficacy, notable adverse effects, and high treatment costs. Thus, there is a pressing need for safer and more effective treatment strategies. In recent years, natural product-based therapies have garnered increasing attention due to their multi-target mechanisms and relatively low toxicity. This review comprehensively summarizes recent advances in the application of natural products for IDD treatment, with a focus on flavonoids (e.g., quercetin, hyperoside), glycosides (e.g., ginsenosides, notoginsenosides), terpenoids (e.g., aucubin, celastrol), phenolic compounds (e.g., curcumin, resveratrol), and alkaloids (e.g., berberine, evodiamine). These compounds exert their therapeutic effects by modulating critical signaling pathways, including Sirtuin-1 (SIRT1), Nuclear Factor-kappa B (NF-κB), Mitogen-Activated Protein Kinase (MAPK), Phosphoinositide 3-Kinase/Protein Kinase B (PI3K/Akt), and Nuclear Factor Erythroid 2–Related Factor 2 (Nrf2). Collectively, they exhibit potent anti-inflammatory, antioxidant, anti-apoptotic, anti-senescence, and regenerative properties. The insights presented herein provide a robust theoretical foundation to support future preclinical and clinical investigations, highlighting the considerable promise of natural products in IDD management.